PEMAKAIAN BAHASA INDONESIA PADA KEMASAN OBAT NONRESEP: ANALISIS BENTUK SINTAKSIS ( - Himyati, Eva (Salingka, 2015)
This article discusses and describes the use of the Indonesian language on nonprescription medicine package through descriptive study. The nonprescriptive medicine package waschoosen because the costumers are abe to get this medicine easily without doctor’s prescription. The source of data were taken from the written message on medicine package then analysis focused on the used of sentence based on Hasan’s opinion. The result of the study found that there were two forms of sentence used to inform the the costumers about the use of medicine. The forms of the sentence were declarative and imperative. The imperative sentences mostly used were forbidden about 40 sentenses, request is 24 sentences, and command is about 8 sentences.